Penerapan Klausul Force Majeure dalam Kontrak Jual Beli pada Masa Pandemi COVID-19: Studi Kasus PT Hasjrat Multifinance (HMF) Cabang Kotamobagu - Siti Zahroh; Sahala Sahat Amudi Sagala; Ramos Kurnia Panggabean; Rayi Kharisma Rajib (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study discusses the application of force majeure clauses in sales contracts during the COVID-19 pandemic, focusing on the case study of PT Hasjrat Multifinance (HMF) Kotamobagu Branch. In this case, the defendants cited the COVID-19 pandemic as a force majeure situation that prevented them from fulfilling their contractual obligations. However, the panel of judges ruled that recognizing the pandemic as a force majeure reason must take into account existing legal provisions and the absence of specific regulations governing pandemics as force majeure in Indonesia at that time. Therefore, this case illustrates the importance of a detailed evaluation of contract clauses and the application of force majeure, taking into account the legal context and facts on the ground. This study also highlights the need for clear and specific force majeure clauses in sales contracts to explicitly regulate extraordinary conditions such as pandemics. Another issue discussed is the possibility of contract renegotiation as a solution when force majeure clauses do not cover pandemic conditions, in order to ensure that the valid execution of contracts can still be realized despite extraordinary obstacles. Thus, this study provides a comprehensive overview of legal issues, practical solutions, and the impact of the COVID-19 pandemic on the fulfillment of sales and purchase contracts in Indonesia, particularly through the legal perspective of the Kotamobagu District Court's decision against PT Hasjrat Multifinance.